Rosas de Sapiranga: histórias e memórias como recurso educacional e de memória para a comunidade social - (:unkn) unknown (Universidade Federal do Pampa, 2025)
The experimental project described in this paper articulates media and education, focusing on culture, memory, and community. Its object of study concerns the references and stories related to roses in the municipality of Sapiranga, Rio Grande do Sul, known as the “City of Roses.” Educational and innovative in nature, the initiative consisted of creating an Instagram profile aimed at sharing stories and images that highlight the symbolic and material presence of roses in the city. The main goal was to identify and disseminate narratives about the representation of roses in Sapiranga, both in their natural and symbolic manifestations, addressing the lack of content that strengthens local identity and the connection between the community and its urban symbol. The research, of a qualitative, exploratory, and descriptive nature, involved interviews, textual and photographic production, and the creation of cards and carousels, which culminated in the development of the profile “Rosas de Sapiranga.” The produced content is publicly available and has potential for pedagogical use in schools as a didactic tool and as a means of valuing cultural memory. It is concluded that the internet and, particularly, social networks – especially Instagram – show significant potential as educational and cultural tools, serving as dynamic spaces for the preservation and dissemination of local memories, and contributing to the understanding of places, their peculiarities, and their histories.
Roses of Sapiranga: stories and memories as an educational and memory resource for the social community
Keywords: Memória; Educação; Sapiranga, RS; Memory; Education; CIENCIAS SOCIAIS APLICADAS